(untitled) (World Bulletin of Management and Law, 2025)
The article highlights the issues of improving marketing management in higher education institutions under the conditions of digital transformation. The rapid development of digital technologies requires a fundamental renewal of marketing strategies in educational institutions. Based on international experience, statistical data, and the case of the higher education system of Uzbekistan, the current situation and development prospects are analyzed.